Contemporary Migration Policies in Chile: The Voices of Public Officials, International Agents and Migrant Collective Representatives (London Journal of Research In Humanities and Social Sciences, 2025)
In recent decades, South American migration within and towards Latin America has grown substantially. In Chile, per official data 1,625,074 foreign nationals were residing in the country in 2023, almost equally divided between genders and mainly located in the Metropolitan Region of Santiago de Chile, with Venezuelans predominating among those who had arrived in the previous 5 years. The present study consists of a qualitative analysis of policy narratives based on ten face-to face in-depth interviews to migration-related policymakers, representatives of international organizations and migrant collectivity spokesmen in Chile. It aims at analysing their understandings of the progress of present migration policies and associated state capacities. Three main framings are identified. The first could be defined as technocratic, centered on producing evidence and implementing the objectives of general or specific policies. The second takes into account migrants subjective experience and shows social awareness of their suffering and of the concrete problems they face daily. The last emphasises the contemporary humanitarian crisis migrants are experiencing and the discriminatory reactions towards them expressed by sectors of the host population and some state officials. It proposes solutions that entail a radical change in the approach towards national security within public policies and state actions. These visions do not necessarily exclude each other; they are sometimes interconnected and complementary.
Keywords: totalitarianism; Croatia; Yugoslavia; Croatian Spring; Praxis; Pluralism; Repression; Human Rights; Social integration; Migration policies; framings; social discrimination; state capacities; frames; policymaking